Euthanasia and physician-assisted suicide: a review from Islamic point of view - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi (Faculty of Medicine, International Islamic University Malaysia, 2012)
Due to globalizing trend of homogenisation of culture, changes in the health care delivery system and market economics infringing on the practice of medicine, there has been a gradual shift in the attitude of the medical community as well as the lay public towards greater acceptance of euthanasia as an option for terminally ill and dying patients. Physicians in developing countries come across situations where such issues are raised with increasing frequency. As the subject has gained worldwide prominence, we want to review this topic from Islamic perspective due to its significance in medical ethics and clinical practice.